Addition of food preservatives to hydroxypropyl methylcellulose-lipid edible coatings to control postharvest penicillium molds of citrus fruit - Valencia-Chamorro, Silvia A.; Pérez-Gago, María B.; Del-Río, Miguel A.; Palou, Lluís (2017)
New hydroxypropyl methylcellulose (HPMC)-lipid edible composite emulsions containing food additives or GRAS compounds with antifungal properties were developed. Film disks containing sodium salts of parabens, potassium sorbate (PS), or sodium benzoate (SB) were the most effective to inhibit in vitro the pathogens Penicillium digitatum and Penicillium italicum, the causal agents of citrus postharvest green and blue molds, respectively. Selected coatings were tested in vivo on ‘Valencia’ oranges and ‘Ortanique’ mandarins to determine their curative (fruit coated after fungal inoculation) and preventive (fruit coated before fungal inoculation) antifungal activity. In general, the curative activity after incubation at 20°C for 7 days was higher on oranges than on mandarins. On coated oranges, coatings prepared with the mixture PS+SB reduced disease incidence and severity up to 85 and 95%, respectively, with respect to uncoated controls. On coated mandarins, the incidence of green and blue molds was reduced by about 65 and 80%, respectively, by the application of a PS+SP (sodium propionate)-based coating. The tested coatings did not provide any preventive activity against both molds. These (HPMC)-lipid edible coatings effectively preserved fruit quality during cold storage and showed promise as nonpolluting commercial alternatives to conventional citrus waxes.